Linearization of Fifth-Order Ordinary Differential Equations by Generalized Sundman Transformations. (2nd January 2018) - Suksern, Supaporn; Naboonmee, Kwanpaka
Abstract : In this article, the linearization problem of fifth-order ordinary differential equation is presented by using the generalized Sundman transformation. The necessary and sufficient conditions which allow the nonlinear fifth-order ordinary differential equation to be transformed to the simplest linear equation are found. There is only one case in the part of sufficient conditions which is surprisingly less than the number of cases in the same part for order 2, 3, and 4. Moreover, the derivations of the explicit forms for the linearizing transformation are exhibited. Examples for the main results are included.